Pengaruh Pola Asuh Orang Tua dan Kontrol Diri terhadap Agresi pada Remaja Awal - Farkhan Nibras Pratama; Zahro Varisna Rohmadani (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to investigate how parental upbringing patterns0and9self-control abilities influence the degree of aggressive behavior in9adolescents. the monetary system shifted to a fiat form free from gold backing. This research adopts a quantitative method through a multiple linear regression model. The subjects involve 250 adolescents aged 13 to 17 years residing in Yogyakarta, selected using the Slovin9method. Data9collection9was0carried9out via a9Likert-scale questionnaire that has undergone validation and reliability testing. Data processing stages include normality evaluation, linearity assessment, and hypothesis testing. The findings indicate that the data meet the normality and linearity criteria. When hypotheses were tested, parental upbringing patterns proved to significantly affect adolescent aggressive behavior (t = 2,889; p = 0,005), as did self-control ability, which showed a strong correlation with aggressiveness (t = 3,759; p = 0,000). Therefore, these results imply that the more positive the upbringing provided by parents and the stronger the adolescents' self-control, the lower the risk of them exhibiting aggressive actions. In other words, both parental upbringing patterns and self-control abilities play a crucial role in reducing the level of aggression in early adolescents.